2019
DOI: 10.1007/s42250-019-00073-y
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Heavy Metals in Urine of Patients and Tissue of Corpses by Atomic Absorption Spectroscopy

Abstract: This study determined the concentrations of some heavy metals (Cd, Pb, Mn, Cu and Zn) in urine samples of patients with kidney, liver and lung related diseases (age 15-70 years); and tissue samples (kidney, liver and lung) that were pathologically abnormal from corpses (age 21-50 years) during autopsies at the Obafemi Awolowo University Teaching Hospitals Complex, Ile-Ife, Nigeria. It also determined the effects of age distribution, gender and life styles on the urine samples of patients with the aforementione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 21 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…Consumption of medicinal plants with excessive accumulation of heavy metals may cause serious health problems such as disrupt the functions of vital organs, glands, kidney and liver, thereby, affecting biological function of these organs [14,15]. However, elements such as lead, cadmium, mercury and arsenic are non-essential and toxic even at low concentrations for humans [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumption of medicinal plants with excessive accumulation of heavy metals may cause serious health problems such as disrupt the functions of vital organs, glands, kidney and liver, thereby, affecting biological function of these organs [14,15]. However, elements such as lead, cadmium, mercury and arsenic are non-essential and toxic even at low concentrations for humans [16].…”
Section: Introductionmentioning
confidence: 99%
“…Several works have been reported on the levels of nutrients including minerals in Moringa oleifera which differ as a function of geographical location where the plant grown, and the outcome displayed that there could be variation in the level of macro-and micro-element in the plant depending on the soil properties of the topographical location where it grows [19,20]. High concentration of heavy metals, above standard permissible limit of WHO can cause serious health problem [16]. Thus, the determination of heavy metals is important.…”
Section: Introductionmentioning
confidence: 99%
“…One of the techniques that can be used for the identification of heavy metals is Atomic Absorption Spectroscopy (AAS), this analytical technique is widely used to determine more than 70 elements in solution and in different matrices, in quantities as low as 10-14 g with reasonable selectivity, little manipulation, and minimum sample size. It can indirectly identify anions and organic compounds [33,34]. This technique is older than ICP-OES (Inductively Coupled Plasma Optical Emission Spectroscopy), and various authors have reported studies comparative with other methods cited in environmental regulations [12,28,38], some mention that it makes it possible to quantitatively determine the chemical elements that constitute a material quickly, precisely, and accurately [7,13,35].…”
Section: Methods For the Characterization Of Heavy Metals In Phytoremediationmentioning
confidence: 99%
“…[ 33,34] Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES)…”
Section: Technique Characteristics Referencesmentioning
confidence: 99%
“…The nephrotoxic effects of lead has been observing at high blood concentrations 1.93 -2.42 μmol L -1 (40-50 μg dL -1 ) [15,18]. The various methods was used for determination lead in different matrix samples [13,19]. The most well-known methods are; flame atomic absorption spectrometry (FAAS) [20], graphite furnace atomic absorption spectrometry (GFAAS) [21], inductively coupled plasma-optical emission spectrometry (ICP-OES) [13], and inductively coupled plasmamass spectrometry (ICP-MS) [22].…”
Section: Introductionmentioning
confidence: 99%